Purification and characterization of extracellular pectinase produced by a newly isolated strain, Aspergillus cervinus ARS2 and its potential application in Citrus sinensis juice clarification - Anil R. Shet; Sharanappa Achappa; Shivalingsarj V. Desai (Kuwait Journal of Science)
This study investigates the purification and characterization of pectinase synthesized by a newly isolated strain, Aspergillus cervinus ARS2, using solid-state fermentation. The crude pectinase, exhibiting a total activity of 5408 IU and a protein content of 214 mg, underwent a systematic purification process that resulted in a purification fold of 1.33 for membrane filtration (50 kDa cut-off), 2.52 for ammonium salt precipitation, 5.77 for dialysis, and an impressive 24.17 for gel filtration chromatography (Sephadex G-75 column), culminating in a purified pectinase with a molecular weight of 37 kDa as determined by sodium dodecyl-sulphate polyacrylamide gel electrophoresis (SDS-PAGE). Characterization of the purified pectinase revealed an optimal incubation time of 40 min, an incubation pH of 4, and stability in acidic conditions (pH 4) over a 5-h storage period. The enzyme exhibited an optimal incubation temperature of 35 °C and maintained stability under the same conditions for 5 h. Kinetic analysis indicated a Michaelis- Menten constant (Km) of 0.78 mg/mL and a maximum velocity (Vmax) of 111.12 IU/mL. The purified enzyme was immobilized using a polyvinyl alcohol-alginate encapsulation method and subsequently utilized in the clarification of Citrus sinensis (orange) juice. Optimization of the juice clarification process, employing full factorial design (FFD) and response surface methodology (RSM), identified optimal conditions of 39.09 °C incubation temperature, 62.12 min incubation time, and an enzyme load of 3.33 mL. These parameters achieved juice clarity of 45.24 ± 1.68 %. These results underscore the potential of the pectinase produced by A. cervinus ARS2 to address the growing demands of the fruit juice industry.